2006
DOI: 10.1002/jat.1175
|View full text |Cite
|
Sign up to set email alerts
|

Naringin, a grapefruit flavanone, protects V79 cells against the bleomycin‐induced genotoxicity and decline in survival

Abstract: The effect of naringin, a grapefruit flavonone was studied on bleomycin-induced genomic damage and alteration in the survival of cultured V79 cells. Exposure of V79 cells to bleomycin induced a concentration dependent elevation in the frequency of binucleate cells bearing micronuclei (MNBNC) and a maximum number of MNBNCs were observed in the cells treated with 50 microg ml(-1) bleomycin, the highest concentration evaluated. This genotoxic effect of bleomycin was reflected in the cell survival, where a concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 99 publications
1
40
0
Order By: Relevance
“…Naringin has been found to protect against mutagenesis and lipid peroxidation [29][30][31][32]. Earlier studies from this laboratory have indicated that naringin reduced the radiation-induced micronuclei formation and chromosomal aberrations in mice and bleomycininduced DNA strand breaks in cultured V79 cells [25,33,34]. It has also been found to protect against the doxorubicin-induced caridiotoxicity without alleviating its antitumor activity in mouse [18].…”
Section: Biochemistry and Molecular Biology Journal Issn 2471-8084mentioning
confidence: 99%
“…Naringin has been found to protect against mutagenesis and lipid peroxidation [29][30][31][32]. Earlier studies from this laboratory have indicated that naringin reduced the radiation-induced micronuclei formation and chromosomal aberrations in mice and bleomycininduced DNA strand breaks in cultured V79 cells [25,33,34]. It has also been found to protect against the doxorubicin-induced caridiotoxicity without alleviating its antitumor activity in mouse [18].…”
Section: Biochemistry and Molecular Biology Journal Issn 2471-8084mentioning
confidence: 99%
“…Naringin (NR) is a bioflavonoid found in grapefruits and other citrus species (Figure 1). It has been shown to exhibit various pharmacological and therapeutic properties, e.g., antimicrobial (Céliz et al, 2011), antimutagenic (Jagetia et al, 2007), anticancer (Li et al, 2013), anti-inflammatory, cholesterol-lowering, and antioxidant effects (Jeon et al, 2002). Few studies have reported the cardioprotective effect of NR against isoproterenol (ISO)-induced myocardium infarction (MI) in rats (Rajadurai & Prince, 2006;Rajadurai et al, 2007).…”
Section: +mentioning
confidence: 99%
“…[10] BLM has been reported to induce DNA damage, point mutations, recombination, chromosome aberrations and micronuclei in diverse organisms, including bacteria, bacteriophage, fungi, drosophila, and mammals. [11] Recently, investigations on MN frequencies support the widely accepted assumption that MN is a product of early events in human carcinogenic processes. [12] Our results showed that all tested concentrations of A. calamus lowered the mutagenic effects of BLM by decreasing MN frequencies with the strongest activity obtained for highest concentration (40 µg/ml).…”
Section: Discussionmentioning
confidence: 96%